Four false dichotomies in the study of teleology. - McShea, Daniel W.; Babcock, Gunnar (Ratio, 2024)
The study of teleology is challenging in many ways, but there is a particular challenge that makes matters worse, distorting the conceptual space that has set the terms of debate. And that is the tendency to think about teleology in terms of certain long‐established dichotomies. In this paper, we examine four such dichotomies prevalent in the literature on teleology, the notions that: 1) Teleological explanations are opposed to mechanistic explanations; 2) teleology must arise from processes operating either internal to an organism or external to it; 3) systems are either alive and teleological, or nonliving and not teleological; 4) humans are teleological, on account of our ability to intend, seek, prefer, etc., while other systems without these capacities are not. Here, we use our own view of goal directedness, field theory, to show for each dichotomy that there is an alternative, a view of teleology that either violates these dichotomies or demands revision of them. What this reveals is not only the dangers of dichotomous thinking, but a widespread lack of clarity about what teleology is.